RELEVANCE EMPLOYABILITY SKILLS OF VOCATIONAL HIGH SCHOOL STUDENTS DEPARTMENT OF KGSP IN DIY TO THE CONSTRUCTION SERVICE INDUSTRY - Susmita Utami; Widarto Widarto; Shilmi Arifah (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
This study aims to prove the importance of employability skills for the construction service industry for graduates of vocational high school majoring in Sanitation Building Construction and Maintenance (KGSP), revealing the implementation of employability skills and their suitability at vocational high school majoring in KGSP in DIY, and describing the level of relevance of employability skills of vocational high school students majoring in KGSP in DIY to the construction service industry. This type of research uses a descriptive quantitative approach and uses a survey method. The research was conducted in vocational schools and the construction service industry in DIY. The research subjects were the head of the company, project manager, engineer, surveyor, and vocational students majoring in KGSP in DIY. Collecting data using observation and questionnaires. The results of the study show: (1) employability skills are very important and needed by the construction service industry for graduates of vocational high school majoring in KGSP obtaining 85.95% with a very important category, employability skills needed by the construction service industry in total are 54 points (2) vocational high school majoring in KGSP implement employability skills obtained 84.01% in the very appropriate category or taught by teachers in schools, the overall employability skills implemented were 45 points (3) the level of relevance of employability skills of vocational students to the world of industrial work obtained 83.3% with a very relevant category.